2018
DOI: 10.18517/ijaseit.8.6.3899
|View full text |Cite
|
Sign up to set email alerts
|

Tannin Extraction from Bark of Rhizophora Mucronata Using Soxhlet and Boiling Techniques

Abstract: Extraction of tannin Rhizophora Mucronata barks by using two methods, which were soxhlet extraction and boiling were demonstrated in this study in order to evaluate the effective technique for extraction. Several parameters such as the type of solvent used, time of extraction, and sample size were specified. The extractant was then evaporated using vacuum rotary evaporator. The percentage of extractives and the characterization of condensed (Stiasny Index) and hydrolyzable tannins were all quantified. The mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Al-Sumri et al (2017), used different particle size rangers to study date extraction of oil for date stones using a soxhlet apparatus, and found the smallest particle size range gave the best results (Al-Sumri et al, 2017). This also agrees with Muhammad Muhhayidin et al ( 2018), who showed that tannin extraction from the bark of Rhizophora mucronata gave highest yields with a 0.5 mm milled bark particle size than with bigger sizes (Muhammad Muhayyidin et al, 2018). These results are also confirmed by the Kruskal-Wallis tests performed.…”
Section: Soxhlet Extractionsupporting
confidence: 91%
See 1 more Smart Citation
“…Al-Sumri et al (2017), used different particle size rangers to study date extraction of oil for date stones using a soxhlet apparatus, and found the smallest particle size range gave the best results (Al-Sumri et al, 2017). This also agrees with Muhammad Muhhayidin et al ( 2018), who showed that tannin extraction from the bark of Rhizophora mucronata gave highest yields with a 0.5 mm milled bark particle size than with bigger sizes (Muhammad Muhayyidin et al, 2018). These results are also confirmed by the Kruskal-Wallis tests performed.…”
Section: Soxhlet Extractionsupporting
confidence: 91%
“…This is agreements with previous studies that have shown that in general a soxhlet extraction is more effective than other techniques. When comparing the soxhlet method with a boiling technique to extract tannins from Rhizophora barks, Muhammad Muhayyidin et al (2018), showed that the soxhlet method was superior to boiling, obtaining 29 wt% and 13 wt% of extractives respectively(Muhammad Muhayyidin et al, 2018) Markom et al (2007). also studied the effects of different extraction methods to obtain tannins from Phyllanthus niruri and showed extraction by soxhlet was the best method for gallic and ellagic acid extractions.…”
mentioning
confidence: 99%
“…In addition, incorporating water to acetone and ethanol did increase the extract yield [35]. On the same line, Muhammad Muhayyidin et al [36] determined that the polar solvents methanol and water increased percentage yields compared to other non-polar solvents. As in other studies, they also suggested that particle size influenced the effectiveness of the extraction, and the larger the particle, the lower the yields obtained.…”
Section: Total Extraction Yield Analysismentioning
confidence: 87%
“…However, there are other factors that should be taken into consideration. Particle size has been shown to influence extraction efficiency: the smallest the size of particle samples, the highest the percentage of yields obtained [34,36,48]. Solvent proportion could also improve polyphenol contents by 50%, as stated by Dos Santos-Ferreira et al [43], Pereira et al [44], and Rhazi et al [49].…”
Section: Extract Composition Analysismentioning
confidence: 96%
“…In comparison, Long-term research on wattle tannin from the bark of the Acacia mearnsii tree, including in vivo activity tests and clinical trials, has now resulted in health food supplement products in Japan that can last up to ten years without side effects [33,34]. Other studies have discovered that Rhizophoraceae extract has a high tannin content as well as antimicrobial activity [35][36][37]. Several studies also found that the antioxidant activity of Rhizophoraceae increased as tannin concentration increased [38][39][40].…”
Section: Introductionmentioning
confidence: 99%